RISIKO DALAM PETERNAKAN AYAM PETELUR: SEBUAH ANALISIS DARI CIMUNING FARM, BEKASI - Lutfiadi, Ridwan; Rahmanto, M. Ikhwan; Purwanto, Rindo; Asyani Listyowati, Esi (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
Risk as an obstacle is always faced in every business, including the Cimuning Farm laying chicken farming business which is also not free from business risks. The aim of this research is to identify sources of production risk, determine the probability value of production risk, determine the impact of production risk, and formulate handling strategies that can be applied to prevent and handle production risks in the Cimuning Farm laying chicken farming business, Bekasi City. The research method is a case study of the Cimuning Farm laying chicken farming business in Bekasi City. Descriptive analysis is used to determine the sources of risk, z-score analysis is used to determine the magnitude of risk probability and risk map analysis to determine preventive and mitigation strategies. The research results show that the sources of production risk at Cimuning Farm are weather, disease and pests. The probability that the weather has an influence is 24.20%, the disease factor is 33.36% and the pest factor is 32.28%. The impact of sources of production risk at Cimuning Farm from the largest to the smallest losses, namely those caused by disease amounting to IDR 5,724,122.00, weather amounting to IDR 1,849,575.00, and pests amounting to IDR 1,011,001.00. Preventive strategies that can be implemented include installing barbed wire around the enclosure walls, and scheduling guard shifts at night. Mitigation strategies that can be implemented include spraying insecticides regularly, cleaning eating and drinking places regularly and administering medicines and vaccines periodically